Social and environmental justice:: a reflection about the sport mega-events in the city of Rio de Janeiro - Vilani, Rodrigo Machado; Machado, Carlos José Saldanha (Sustainability in Debate, 2014)
The spatial reorganization of the municipality of Rio de Janeiro, aimed at adapting the city to mega sporting events, demanded removals, infrastructure investments, among other actions. The aim of this paper is to strengthen the legal and political debate on the right to the city for its inhabitants through an assessment of the extent of the proposed urban interventions from the current framework of environmental justice and the historical process of socio-spatial segregation embodied in Rio's slums. The analysis of the Olympic city will be based on qualitative and quantitative methodology of primary and secondary data on sanitation and removals occurred because of the mega-events. Among the findings it can be highlighted the environmental backlash generated by public policies implemented in the investment cycle. To conclude the paper weaves general and specific considerations aimed at strengthening the process of preparation and evaluation of public policies as well as to construction of a sustainable city model in the municipality of Rio de Janeiro.